Comparisonal Analysis Of Debt To Equity Ratio (DER) Between Pt. Bank Mega, Tbk And Pt. Bank CIMB Niaga, Tbk - Tandiarrang, Edward Jumadi; Nurhayati, Nurhayati (Invoice : Jurnal Ilmu Akuntansi, 2022)
This study aims to determine whether there are differences in the Debt To Equity Ratio (DER) between PT. Bank Mega, TBK and PT. Bank CIMB Niaga, TBK. The data used in this study is quantitative data from secondary data sources which are then processed. This type of research is comparative, comparative research is used to determine the difference in Debt To Equity Ratio (DER) between PT. Bank Mega, TBK and PT. Bank CIMB Niaga, TBK. The research instrument used is a list of tables containing data on total debt and total equity of PT. Bank Mega, TBK and PT. Bank CIMB Niaga, TBK. The population used in this study were all financial statements of PT. Bank Mega, TBK since being listed on the IDX from 1969 to 2020 for 51 years and PT. Bank CIMB Niaga, TBK since being listed on the IDX from 1989 to 2020, which is 31 years. The sample in this study is the financial statements of PT. Bank Mega, TBK and PT.Bank CIMB Niaga, TBK for 10 years, from 2011 to 2020. The sampling technique used in this study is a purposive sampling technique with the criteria (1) financial statement data is available for 10 consecutive years namely the years 2011-2020 (2) the 10-year sample data already represents the existing population data for research needs. Data collection techniques used are documentation and literature study. The data analysis technique used in this research is descriptive analysis and statistical analysis using independent sample t test. The results showed that there was no difference in Debt to Equity Ratio (DER) between PT. Bank Mega, TBK and PT. Bank CIMB Niaga, TBK.